Gewerkschaften im deutschen Einheitsprozess Möglichkeiten und Grenzen in Zeiten der Transformation - Brunner, Detlev (Forschung aus der Hans-Böckler-Stiftung, 2017)
The role of the unions in the process of German unity has so far received little attention. From the beginning, they were among the forces that helped shape the social and economic transformation of East Germany. In the volume's volume, scientists and formerly active people from East and West - starting from their respective different perspectives - consider the possibilities, successes and limits of trade union politics and trade union action. The focus is on trade union contacts before 1989, the phases of upheaval and unification, the work of the Treuhandanstalt and tariff policy. The effects of the transformation process are also elaborated.